1983
DOI: 10.1038/bjc.1983.56
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human colon carcinoma cell lines isolated from a single primary tumour

Abstract: Summary The initiation of a cultured human colon carcinoma line on a feeder layer of confluent fibroblasts is described. Attempts to initiate cultures without fibroblast feeder layers were not successful. Two sub-lines (designated HCT C and HCT C Col) were isolated and weaned from cells growing on the surface of the feeder layer. The sub-lines had different morphologies, secreted different levels of carcinoembryonic antigen (CEA) into the medium of confluent cultures and had slightly different karyotypes. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 7 publications
(4 reference statements)
1
44
0
Order By: Relevance
“…To characterize the features of the CAFs, we showed by conditioned-medium proliferation assays that CAF-derived medium promoted cancer cell proliferation to a greater extent than other fibroblastderived medium, likely by secreting more growthpromoting factors (Gleave et al, 1991). Irrespective of the origin of fibroblasts, previous reports have shown that fibroblasts enhance the growth of cancer cells and are often required to establish tumor by providing a feeding layer (Brattain et al, 1982;Picard et al, 1986;Camps et al, 1990;Gleave et al, 1991). In our conditioned-medium assays, without direct interaction between cancer cells and fibroblasts, we also observed a clear-cut enhancement of cancer cell growth by all fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…To characterize the features of the CAFs, we showed by conditioned-medium proliferation assays that CAF-derived medium promoted cancer cell proliferation to a greater extent than other fibroblastderived medium, likely by secreting more growthpromoting factors (Gleave et al, 1991). Irrespective of the origin of fibroblasts, previous reports have shown that fibroblasts enhance the growth of cancer cells and are often required to establish tumor by providing a feeding layer (Brattain et al, 1982;Picard et al, 1986;Camps et al, 1990;Gleave et al, 1991). In our conditioned-medium assays, without direct interaction between cancer cells and fibroblasts, we also observed a clear-cut enhancement of cancer cell growth by all fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Xenografts of colon tumors in nude mice have been produced either directly from surgical specimens [18,19,[24][25][26][27] or from cell lines established in culture [25,[27][28][29][30]. Whether fresh specimens or cell lines provide the better model for HCC in nude mice is still debated.…”
Section: Human Colon Carcinoma Xenografted Into Nude Micementioning
confidence: 99%
“…However, for none of the long-established colorectal cancer lines readily available is status at critical oncosuppressor loci known. Moreover long-established lines commonly acquire additional genetic rearrangements during culture (Brattain et al, 1983;Park et al, 1987), which may not be reversible by correction of the original oncosuppressor defect alone. We therefore set out to develop a series of lines from primary colorectal tumours, defined both in terms of status at oncosuppressor loci on chromosomes 5, 17 and 18, and the stability of each locus on serial passage.…”
mentioning
confidence: 99%